P133 HLA-ANTIGENS and disease manifestation in a cohort of 600 southern french patients with psoriatic arthritis. (21st February 2018) - Massy, E; Picard, C; frassati, C; pedini, P; martin, M; Auger, I; Roudier, J; Balandraud, N
Abstract : Introduction: Currently, there is no biomarker available to diagnose psoriatic arthritis (PsoA). Genome wide association studies showed that the majority of PsoA loci are shared with PsoC. 1 However, PsoA has a strong familial predisposition, more so than PsoC as was shown in an Icelandic population. 2 In the GWAS performed in UK and Germany, the strongest genetic locus is located within the major histocompatibility complex (MHC). 3, 4 No studies have been performed in southern Europe Objectives: The primary objective of our study was to focus on the HLA class I and II alleles found in a cohort of 600 French patients with PsoA clinically well characterised, compared to a control cohort. The secondary objective was to compare two clinical subsets of PsoA, one axial and one peripheral, to test which genotype determines these phenotypes. Methods: 600 patients from the Rheumatology department, St. Marguerite's Hospital, Marseilles, who fulfilled the CASPAR criteria for PsoA, underwent clinical, radiographic and laboratory investigations. HLA Class I and Class II alleles were genotyped. A cohort of 2346 healthy blood donors (HBD) was also tested. Results: Comparison between the PsoA population and controls showed one set of alleles significantly associated with PsoA; HLA-B*27, B*21(B*50), C*06 and with a weak significance HLA-A*01, A*25, B*13. Within the PsoA population, two genetically different subsets determine two different clinical subtypes: Peripheral disease was significantly associated with -C*06 in disequilibrium linkage with -B*13 and -DR*07, independently associated with HLA-A*01, -B*21 and -B*17. Axial disease was significantly associated with HLA-B*27 in disequilibrium linkage with C*01 and -C*02. Conclusions: This is the first and the largest study ever realised in southern Europe. It lead to conclude that PsoA is genetically heterogeneous. We found that PsoA is divided in two genetically and phenotypically relevant subgroups, one axial group with HLA-B*27 predominance very close to Ankylosis spondylitis and one peripheral group with HLA-C*06 predominance. Other HLA alleles within the MHC are also implied. The clinical utility of HLA typing in PsoA should be further addressed in larger studies. References: . Stuart PE, Nair RP, Tsoi LC, et al. Genome-wide association analysis of psoriatic arthritis and cutaneous psoriasis reveals differences in their genetic architecture. Am J Hum Genet2015;97:816–36. doi:10.1016/j.ajhg.2015.10.019 . Chandran V, Schentag CT, Brockbank JE, et al. Familial aggregation of psoriatic arthritis. Ann Rheum Dis2009;68:664–7. doi:10.1136/ard.2008.089367 . Rahman P, Elder JT. Genetics of psoriasis and psoriatic arthritis: A report from the GRAPPA 2010 annual meeting. J Rheumatol2012;39:431–3. doi:10.3899/jrheum.111242 . Bowes J, Budu-Aggrey A, Huffmeier U, et al. Dense genotyping of immune-related susceptibility loci reveals new insights into the genetics of psoriatic arthritis. Nat Commun2015;6:6046. doi:10.1038/ncomms7046 Disclosure of interest: None declared